The importance of neutral zone in fully edentulous case with highly resorbed ridge - Salim, Irvan; Dahlan, Agus (Indonesian Journal of Prosthodontic, 2020)
Full edentulous is one of the most challenging cases for prosthodontist. One of the difficulties in treating that cases is the limitations in support and retention, especially in cases with highly resorbed ridge where the denture bearing area avalaible is minimum.One of the techniques to achieve the retention is by using the neutral zone tech-nique. Neutral zone is the area where the displacing forces of the lips, cheeks, and tongue are in balance. It is in this zone that the natural dentitions lie and this is where the artificial teeth should be positioned. This area of mi-nimal conflict may be located by using the neutral zone technique. The artificial teeth can then be set up in the correct positions. By using this concept it will be able to achieve retention, stability and support. This case report will share the usage of the neutral zone technique in treating fully edentulous ridge with highly resorbed ridge.